Prophylactic and therapeutic efficacy of dietary Nigella sativa L. supplementation against hepatopathy in rats induced by kavalactone and kavalactone with alcohol - Hasan, Mohammed Abdulabbas (2018)
Despite having potent psychoactive properties, the hepatotoxic effects of kavalactone (KL) is well documented. It has been banned in Europe and Canada with cautions and advisories by the US FDA. A study was designed to investigate the prophylactic and therapeutic efficacies of dietary Nigella sativa (NS) supplementation on the oral sub-acute and sub-chronic toxicity of 800 mg/kg KL with or without alcohol in rats. The idiosyncratic toxicity of KL appears to have an unclear risk-to-benefit ratio. Therefore, it is critical to identify and determine any possible adverse side effects of KL products that could potentially lead to toxicity especially when taken with alcohol. Seventy-two, female Sprague-Dawley rats, were divided randomly into two experimental studies, viz; prophylactic and therapeutic efficacy of NS supplementation against KL with or without alcohol. Rats were equally allotted into nine groups comprising six animals each, namely negative control (NCx1), positive control (NCx2), alcohol (EtOH), Nigella sativa (NS), kavalactone (KL) and alcohol plus kavalactone (EtOH+KL) and NS-preventing groups {(NS+KL), (NS+EtOH) and (NS+KL+EtOH)}. The other experimental trial is aimed at investigating the therapeutic effect of NS in treatment and reducing the hepatic lesion progression and establishment, wherein rats were equally assigned into nine groups comprising six animals each, namely control groups {(NCx1), (NCx2), (EtOH), (NS), (KL) and (EtOH+KL)} and NS-treatment groups {(NS+KL), (NS+EtOH) and (NS+KL+EtOH)}. Rats in the NS-preventive groups were given NS at doses of 100 mg/kg (b.w)/per day orally for three consecutive days prior to the onset of hepatotoxicity induction and then with the course of KL (alone or in combination) with EtOH as a prophylactic measure. On the other hand, those in the {(NS+KL), (NS+EtOH) and (NS+KL+EtOH)} treatment groups were given NS at the same dose, together with KL at 800 mg/kg/day (orally) (alone or in combination) with EtOH as a therapeutic measure. The sampling was done at weeks (W0), (W1), (W2) and (W3) in both experiments as a sub-acute trial and also at weeks (W6), (W9), (W12) and (W14) as a sub-chronic study for both experiments. Exsanguinations were done following euthanasia followed by procurement of the liver at 3rd and 14th weeks post-treatment for the prophylactic and therapeutic study as sub-acute and sub-chronic trials. Rats receiving KL plus EtOH showed the severest bodyweight changes, clinical signs (abnormal breathing, ataxia, lethargy, loss of appetite and incoordination), oxidative stress, and pathology of the liver (hepatocellular necrosis, hepatocellular hypertrophy with high proliferation of sER). Furthermore, dietary supplementation of NS for almost 14 weeks showed that NS exhibited an anti-oxidative stress effect in the liver as evidenced seen from the low ALT. In response to antioxidant enzymes, especially in preventing groups, an increase in SOD and GSH-Px indirectly has alleviated oxidative stress leading to a much lower MDA. The NS reduces the incidence of hepatopathy especially fatty degeneration, hepatomegaly, sER and peroxisome proliferation for more than 50%. This study demonstrated that dietary supplementation of NS at a dose of 100 mg/kg/day orally, significantly (p <0.01) reduces serum lipid profile together with suppression of oxidative damage and therefore alleviates hepatopathy lesions. Ethanol potentiated the sedative and hypnotic activity of KL and markedly increased the toxicity whereas, KL toxicity is likely due to herbal drug interaction rather than direct liver toxicity from KL alone. Finally, NS is highly efficacious in abating oxidative stress and cellular damage in rats.